2019
DOI: 10.1016/j.cll.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

We Cannot Do It Alone

Abstract: Infectious diseases by definition spread and therefore have impact beyond local hospitals and institutions where they occur. With increasingly complex and worrisome infectious disease evolution including emergence of multidrug resistance, regional, national, and international agencies and resources must work hand in hand with local clinical microbiology laboratories to address these global threats. Described are examples of such resources, both existing and aspirational, that will be needed to address the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We hope that this article may be a reference for clinical laboratories to justify this approach to laboratory inspectors in the interim. We make further note that we (6) and at least one other set of authors, more tentatively (8), have previously suggested such an approach.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…We hope that this article may be a reference for clinical laboratories to justify this approach to laboratory inspectors in the interim. We make further note that we (6) and at least one other set of authors, more tentatively (8), have previously suggested such an approach.…”
mentioning
confidence: 77%
“…The requirement for laboratories to perform an accuracy and precision study using the common rule of thumb of 30 isolates is extremely underpowered from a statistical perspective (6). For example, the FDA guidance on approval of AST devices highlights that such a small study would be inappropriate to characterize the very major, major, and minor error rates for a method (7).…”
mentioning
confidence: 99%
“…Our study identified early laboratory markers associated with a poor disease prognosis. Providing access to laboratory tests in areas with a high prevalence of dengue could facilitate the diagnosis and identification of patients with poor prognosis, with the aim of providing them with greater surveillance and timely treatment [ 51 ].…”
Section: Discussionmentioning
confidence: 99%